Unraveling the origin of strain-induced precipitation of M23C6 in the plastically deformed 347 Austenite stainless steel - Hong, Sung-Min; Kim, Myung-Yeun; Min, Dong-Joon; Lee, Kyu-ho; Shim, Jae-Hyeok; Kim, Dong-Ik; Suh, Jin-Yoo; Jung, Woo-Sang; Choi, In-Suk (ELSEVIER SCIENCE INC, 2014)
In this research, the phenomenon of strain-induced precipitation of M-23 (M = Cr, Fe, Mo) C-6 precipitates in 347 austenite stainless steel was systematically studied. During annealing at 650 degrees C, the experimental results exhibited significantly earlier formation of M23C6 precipitates in the plastically strained specimen, than in the no-strain specimen. The various microstructural characterizations showed that the accelerated formation of M23C6 precipitates occurred around deformation bands that were generated by deformation twinning. Extensive investigation suggested that the strain-induced precipitation of M23C6 is attributed to the formation of strain-induced alpha' martensite during plastic deformation near deformation bands. (C) 2014 Elsevier Inc. rights reserved.
Keywords: INDUCED MARTENSITE; DEFORMATION; SENSITIZATION; MORPHOLOGIES; MECHANISM; FAILURE; TUBES